Kajian Teologis Pengkhotbah 11: 9-10 Berkaitan dengan Prinsip You Only Live Once (YOLO) pada Generasi Muda - Meichella Yosepha Eunike; Farel Yosua Sualang (Jurnal Pistis: Teologi dan Praktika, 2023)
Principles can be defined as principles, truths that become the basis for thinking, acting, and behaving. Today's young generation also has principles that they hold as a reference in life, one of which is the principle of YOLO which can be defined differently from one another. The problem is that the different understanding of the YOLO principle creates contradictions so that two people with the same principle can have very contradictory ways and achievements in life between the positive and negative sides. Misperceptions in understanding the YOLO principle can affect the moral depravity, mindset, and lifestyle of the younger generation. Therefore, by using a qualitative method with a literal study approach, the researcher will conduct research to find how the YOLO life principle is theologically linked to the book of Ecclesiastes 11: 9-10. At the end of the research, it is found that the YOLO life principle does not contradict the truth of God's word if it is accompanied by accountability to God.